Ergonomi Duduk yang Benar untuk Mencengah Terjadinya Low Back Pain (LBP) di Kelurahan Mayang Mangurai Kota Jambi - Putra Hadi; Wanti Hasmar (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
One of the musculoskeletal disorders that often occurs due to incorrect ergonomics is low back pain. Low back pain (LBP) is a pain syndrome that occurs in the lower back region which is the result of various causes including abnormalities of the spine or spine from birth, trauma, tissue changes, and the influence of gravity. Community service activities will be held in April-June 2021 with discussion methods and delivering materials and leaflets related to the introduction of ergonomics in the correct sitting position in order to reduce the impact of low back pain. This Community Service (PKM) aims to be used as a source of knowledge for recitation mothers at the Nurul Al-Ikhlas mosque. The results of the evaluation through the question and answer were that the study mothers had understood the introduction of ergonomic sitting to prevent LBP